The chromatin binding factor Spn1 contributes to genome instability in Saccharomyces cerevisiae - Thurston, Alison K., author; Stargell, Laurie, advisor; Bailey, Susan, committee member; DeLuca, Jennifer, committee member; Hansen, Jeffrey, committee member; Luger, Karolin, committee member (Colorado State University. Libraries, 2018)
Maintaining the genetic information is the most important role of a cell. Alteration to the DNA sequence is generally thought of as harmful, as it is linked with many forms of cancer and hereditary diseases. Contrarily, some level of genome instability (mutations, deletions, amplifications) is beneficial to an organism by allowing for adaptation to stress and survival. Thus, the maintenance of a "healthy level" of genome stability/instability is a highly regulated process. In addition to directly processing the DNA, the cell can regulate genome stability through chromatin architecture. The accessibility of DNA for cellular machinery, damaging agents and spontaneous recombination events is limited by level of chromatin compaction. Remodeling of the chromatin for transcription, repair and replication occurs through the actions of ATP remodelers, histone chaperones, and histone modifiers. These complexes work together to create access for DNA processing and to restore the chromatin to its pre-processed state. As such, many of the chromatin architecture factors have been implicated in genome stability. In this study, we have examined the role of the yeast protein Spn1 in maintaining the genome. Spn1 is an essential and conserved transcription elongation factor and chromatin binding factor. As anticipated, we observed that Spn1 contributes to the maintenance of the genome. Unexpectedly, our data revealed that Spn1 contributes to promoting genome instability. Investigation into a unique growth phenotype in which cells expressing a mutant form of Spn1 displayed resistance to the damaging agent, methyl methanesulfonate revealed Spn1 influences pathway selection during DNA damage tolerance. DNA damage tolerance is utilized during replication and G2 to bypass lesions, which could permanently stall replication machinery. This pathway congruently promotes and prevents genome instability. We theorize that these outcomes are due to the ability of Spn1 to influence chromatin structure throughout the cell cycle.
Keywords: DNA damage tolerance; methyl methanesulfonate; yeast; genome instability; chromatin binding factor; Spn1